CONTENT QUALITY, RELIGIOUS CONSCIOUSNESS, AND BRAND AWARENESS: THE EMPIRICAL EVIDENCE ON ISLAMIC SHARIA PRODUCT - Raharja, Bayu Sindhu (Jurnal Aplikasi Manajemen, 2021)
Technological development pushes the significant role of content in marketing communication. This research aims to seek the effect of content quality on Islamic sharia products' brand awareness. It is attractive as consumers of Islamic sharia products have more unique characteristics than consumers as usual. For instance, the consumers of Islamic sharia products restrict themselves from consuming a product that is not proper to their religious consciousness. Therefore, this work attempts to introduce the other antecedent variable of spiritual consciousness beyond content quality to reveal how brand awareness appears in Islamic sharia products. So, by employing the covariance-based structural equation model, this study examines the data from 1,429 members of the Islamic community in Indonesia. The result shows that content quality has no significant effect on brand awareness. Instead, the variable of religious consciousness has a positively considerable impact on predicting the level of brand awareness in Islamic sharia product consumption. Indeed, it is decent with the proposed hypothesis of this research. This result shed light on the kind of practice and theoretical implications, such as the empirical test of reconceptualization of the S-O-R model in consumer behavior, implementation of marketing strategy, and development marketing theory on Islamic sharia products. It also gives insight into the development of consumer behavior theory. Further research should extend and focus on consumer purchasing decisions.